A simple method to fabricate N-doped hierarchical porous carbon for supercapacitors. Issue 2 (4th May 2019) - Zhang, Jinliang; Zhang, Wenfeng; Liu, Junqing; Liang, Wenbin; Yang, Yusheng
Abstract: Direct carbonization of nitrogen-containing precursors combined with activation is an effective way to prepare nitrogen-doped hierarchical porous carbon. The most common activation agents being used such as KOH and NaOH may cause serious corrosion to the manufacturing equipment. To resolve this problem, a facile approach has been developed to prepare phenolic resin-derived nitrogen-doped hierarchical porous carbon using sodium acetate as the activation agent and hexamethylenetetramine as the nitrogen source. Acting as an in situ activation agent, sodium acetate is less corrosive. The results show that the sample obtained at 900°C (PHS-900) reaches a maximum specific surface area (SBET ) of 1591 m 2 g −1 . Benefiting from the optimum balance between high nitrogen content (5.41 at.%) and relatively large surface area (827 m 2 g −1 ), the optimal sample PHS-700 exhibits a high specific capacitance of 352 F g −1 when it is used as an electrode in 7 M KOH aqueous electrolyte with a three-electrode system. Furthermore, it also shows excellent long-term stability in a two-electrode cell (95.3% retention after 10 000 cycles). The good electrochemical performance of the samples and the low corrosion, template-free preparation make it a promising strategy to fabricate nitrogen-doped hierarchical porous carbon for supercapacitor electrode materials.